Problematika pengembangan kepustakaan Islam: studi kasus di empat perpustakaan Perguruan Tinggi Keagamaan Islam Negeri (PTKIN) Jawa Timur - Mufid Mufid; Ari Zuntriana (IAIN Ponorogo, 2019)
Introduction. This study aims to examine the Islamic collection development process conducted by 4 (four) Islamic universities’ libraries in East Java, including selection criteria and tools, the use of the collection, and challenges faced by the librarian Data Collection Method. Using a mixed-methods approach with surveys and interviews, four head of libraries and 338 students participated in this research. Analysis Data. Data from the questionnaire were analyzed using descriptive quantitative analysis method while the qualitative data from interviews were analyzed using the thematic analysis technique. Results and Discussions. The results showed that the libraries did not have any written collection development policies. The four libraries have used the right selection tools, but most of them have not utilized reviews of books based on online sources and social media. At present, the four libraries have not had any special subjects which potentially emerged as a distinction of the libraries’ collection. Nevertheless, there has been a plan to develop such a special subject of Islamic collection. The use of Islamic literature collections among students were considered in medium level of use. The challenges in developing Islamic literature collections are sourced both from internal and external sources. Internally, the library has not evaluated their collection development policies. While the low participation of lecturers in the development of library collections emerged as obstacles from external sources. Conclusions. Based on the findings, it can be concluded that the libraries involved in this study still needs improvements in some areas.